2013
DOI: 10.1007/s10856-013-4957-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomimetic hydroxyapatite/alginate nanocomposite fibrous scaffolds for bone tissue regeneration

Abstract: Hydroxyapatite/alginate nanocomposite fibrous scaffolds were fabricated via electrospinning and a novel in situ synthesis of hydroxyapatite (HAp) that mimics mineralized collagen fibrils in bone tissue. Poorly crystalline HAp nanocrystals, as confirmed by X-ray diffractometer peak approximately at 2θ = 32° and Fourier transform infrared spectroscopy spectrum with double split bands of PO4(v 4) at 564 and 602 cm(-1), were induced to nucleate and grow at the [-COO(-)]-Ca(2+)-[-COO(-)] linkage sites on electrospu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 39 publications
0
67
0
2
Order By: Relevance
“…Carbonate, silicates, and magnesium among other ions, may replace hydroxyl or phosphate groups of the apatite structure. Investigators have attempted to produce alginate [38], strontium [39], silicon [40], carbonate and magnesium [4146] substituted synthetic HA in an effort to produce HA that more closely resembles the mineral content of native bone, enhancing bioactivity and osteoconduction (Biomimetic ceramic substitutes) [47]. Although there are few of products made of biomimetic HA in the clinical use at this time, the research is ongoing on this direction and biomimetic HA substitution will likely remain one of the most promising area of research.…”
Section: Hydroxyapatite and Tricalcium Phosphatementioning
confidence: 99%
“…Carbonate, silicates, and magnesium among other ions, may replace hydroxyl or phosphate groups of the apatite structure. Investigators have attempted to produce alginate [38], strontium [39], silicon [40], carbonate and magnesium [4146] substituted synthetic HA in an effort to produce HA that more closely resembles the mineral content of native bone, enhancing bioactivity and osteoconduction (Biomimetic ceramic substitutes) [47]. Although there are few of products made of biomimetic HA in the clinical use at this time, the research is ongoing on this direction and biomimetic HA substitution will likely remain one of the most promising area of research.…”
Section: Hydroxyapatite and Tricalcium Phosphatementioning
confidence: 99%
“…Moreover, HA has the potential to induce hMSCs differentiation into osteogenesis without any addition of growth factors and increase the ALP activity along with osteocalcin expression and mineralization [131]. It also enhances the surface topography of the scaffolds, promotes the growth of cells, adhesion, proliferation and differentiation [132][133][134]. The fabrication of Chitosan/HA biocomposite substitutes for bone tissue formation revealed that spherulites containing calcium and phosphorus is the major component in calcium phosphate apatite known as mineral phase of bone.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In particular, alginate takes a predominant place due to its biocompatibility, biodegradability, and relatively low cost for mass production [11]. These unique properties have enabled alginate to be used in many biomedical applications such as drug delivery and skin/bone scaffolds [11, 12]. Alginate is a linear polysaccharide copolymer composed of two sterically different repeating units of β -d-mannuronate (M unit) and α -L-glucuronate (G unit) in various M/G ratios.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, incorporating micro-/nanofillers into polymeric fibres enables the production of multifunctional scaffolds with enhanced mechanical properties and other vital characteristics such as antimicrobial and anti-inflammatory characteristics of ECM scaffolds. To date, different types of micro-/nanofillers such as hydroxyapatite (HA) [12, 17], chitin whiskers [18], ZnO [19], and Ag nanoparticles [20] have been used to reinforce electrospun alginate nanofibrous scaffolds. With the aforementioned requirements in reinforcing alginate nanofibrous scaffolds, it is essential to widen the research scope by evaluating different types of nanofillers to enhance the mechanical strength of alginate scaffolds.…”
Section: Introductionmentioning
confidence: 99%